Husserl’s Ideen
XIV, 498 p.
Keywords: This collection of more than two dozen essays by philosophy scholars of international repute traces the profound impact exerted by Husserl’s Meisterwerk, known in its shortened title as Ideen, whose first book was released in 1913. Published to coincide with the centenary of its original appearance, and fifty years after the second book went to print in 1952, the contributors offer a comprehensive array of perspectives on the ways in which Husserl’s concept of phenomenology influenced leading figures and movements of the last century, including, among others, Ortega y Gassett, Edith Stein, Martin Heidegger, Aron Gurwitsch, Ludwig Landgrebe, Dorion Cairns, Simone de Beauvoir, Jean-Paul Sartre, Maurice Merleau-Ponty, Jacques Derrida and Giles Deleuze. In addition to its documentation and analysis of the historical reception of these works, this volume also illustrates the ongoing relevance of the Ideen, offering scholarly discussion of the issues raised by his ideas as well as by the figures who took part in critical phenomenological dialogue with them. Among the topics discussed are autism, empathy, the nature of the emotions, the method and practice of phenomenology, the foundations of ethics, naturalism, intentionality, and human rights, to name but a few. Taken together, these specially commissioned original essays offer an unrivaled overview of the reception of Husserl‘s Ideen, and the expanding phenomenological enterprise it initiated. They show that the critical discussion of issues by phenomenologists continues to be relevant for the 21st century.